Предмет: Алгебра, автор: vladcgy

Найти производную

1)frac{15}{(6x-4)^{10}}

2)y=x^{x}

3)y=y=frac{x^{2}+1}{x+1}

4)y=y=frac{5}{x^{2}}

5)2x^{3}-x+pi

Ответы

Автор ответа: dtnth
0

1) (frac{15}{(6x-4)^{10}})'=(15(6x-4)^{-10})'=\ 15*((6x-10)^{-10})'=\ 15*frac{(6x-10)^{-10-1}}{-10-1}*(6x-10)'=\ frac{-15}{11(6x-4)^{11}}*6=-frac{90}{11(6x-10)^{11}}

 

2) y=x^x=e^{x ln x}

y'=(e^{xlnx})'=(e^{xlnx})*(xln x)'=x^x*( x(ln x)'+(x)'ln x)=x^x*(x*frac{1}{x}+1*ln x)=x^x*(ln x+ 1)

 

3) y=frac{x^2+1}{x+1}

y'=(frac{x^2+1}{x+1})'=frac{(x^2+1)'*(x+1)-(x^2+1)*(x+1)'}{(x+1)^2}=\ frac{2x*(x+1)-(x^2+1)*1}{(x+1)^2}=frac{2x^2+2x-x^2-1}{(x+1)^2}=frac{x^2+2x-1}{x^2+2x+1}

 

4) y=frac{5}{x^2}

y'=(frac{5}{x^2})'=(5x^{-2})'=5(x^{-2})'=5*frac{x^{-2-1}}{-2-1}=-frac{5}{3x^3}

 

5) (2x^3-x+pi)'=(2x^3)'-(x)'+(pi)'=2(x^3)'-1+0=2*3x^2-1=6x^2-1

Похожие вопросы
Предмет: Литература, автор: Аноним